PENDAYAGUNAAN ZAKAT SEBAGAI UPAYA PENGENTASAN KEMISKINAN (Studi di Baznas Provinsi Jawa Tengah) - Abdul Aziz (Universitas Semarang, 2016)
Zakat is a religious “maaliyah ijtima’iyah”, worship associated with theproperty, which has a position is very important to improve the welfare of thecommunity, if properly managed, trustworthy, transparent Shari'a compliantIslamiyah, both collection and distribution. Suspected not optimal zakat becausethe government does not have specific policies to make zakat as a source of state revenues. However, if the charity has shown remarkable function as a tool of poverty and pensejahtera pengentas people, the government could begin to look to charity as a major instrument in the nation's economy.The problem in this research is the utilization of zakat what is appropriateas the fight against poverty? And how is ideally Baznas utilization of zakat inCentral Java province attempted to alleviate poverty? The purpose of this studywas to determine the utilization of zakat is appropriate as the fight againstpoverty, and to determine the utilization of zakat in Central Java province Baznasstrived for poverty alleviation.The method used in this research is juridical empirical research, theresearch refers to the norms and principles of law contained in legislation andjudicial decisions and adjusted to actual conditions. Specifications of this research is descriptive analytical research, a study that tried to illustrate the legal issues, legal and studying it or analyze it according to the needs of the research in question, namely on the Empowerment of charity as an effort to increase poverty.The data analysis used is qualitative analysis, which, after collecting data,processing is done, analyzing and constructing thoroughly, systematicallydescribes the relationship between different types of data. Further data iscompleted and processed, and then analyzed descriptively. So as to provide asolution to the problems in this study, which is about the Empowerment Zakat forPoverty Reduction Efforts? Baznas utilization of zakat in Central Java province is not suitable as reducing poverty. Because until now only zakat profession is maintained and only a couple of the Local Government Unit (SKPD) only in Central Java. Poverty is not just caused by natural factors alone, but also equitable development factors influence on this issue. One solution is to empower community-based charity. In effect, alleviating poverty is to alleviate the cause, either individuals or groups in society.